The association of vitamin D with knee osteoarthritis pain: an analysis from the Osteoarthritis Initiative database - Ankai Zuo; Qiufeng Jia; Meirong Zhang; Xinjie Zhou; Tieshan Li; Lin Wang (Scientific Reports)
Abstract Knee osteoarthritis (KOA) is a major cause of disability in the elderly, with its pain primarily driving medical consultations. Despite numerous studies, the role of Vitamin D in managing KOA pain remains inconclusive. This study seeks to explore the association between serum Vitamin D levels and WOMAC pain scores, providing new insights into potential treatment strategies for KOA. Utilizing data from the Osteoarthritis Initiative (OAI) database, we conducted a cross-sectional analysis involving 524 participants. Serum levels of 25-hydroxyvitamin D were measured using liquid chromatography-tandem mass spectrometry. WOMAC pain scores served as the dependent variable. Multivariable linear regression models and restricted cubic splines were employed to assess the relationship between Vitamin D levels and KOA pain, with subgroup analyses stratified by sex. Higher Vitamin D levels were significantly associated with lower WOMAC pain scores in males across all models. For females, no significant associations were observed. The analysis suggests a nonlinear relationship between Vitamin D levels and KOA pain in the general cohort, which becomes non-significant after adjustment for covariates. Our findings indicate that Vitamin D is associated with reduced pain in male patients with KOA, highlighting a potential sex-specific therapeutic approach. The results warrant further investigation through longitudinal studies and randomized controlled trials to substantiate Vitamin D supplementation as a viable treatment for reducing KOA pain in males.